2002
DOI: 10.1038/sj.onc.1205530
|View full text |Cite
|
Sign up to set email alerts
|

Cre-loxP chromosome engineering of a targeted deletion in the mouse corresponding to the 3p21.3 region of homozygous loss in human tumours

Abstract: Chromosomal deletions are a common feature of epithelial tumours and when further de®ned by homozygous deletions, are often the location of tumour suppressor genes. Deletions within the short arm of chromosome 3 occur very frequently in human carcinomas: a minimal region of loss at 3p21.3 (the Luca) region has been de®ned by overlapping homozygous deletions in lung and breast cancer cell lines. Using a rapid strategy for Cre-loxP chromosome engineering, a deletion of approximately 370 kb was created in the mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 21 publications
(26 reference statements)
0
20
0
Order By: Relevance
“…For one, work in other organisms has shown that CRE is capable of excision and recombination over huge distances [50,12] or even between different chromosomes [13]. In T. brucei, this approach could be used, for example, to delete large tandem gene arrays.…”
Section: Extensions Of Cre/loxpmentioning
confidence: 99%
See 1 more Smart Citation
“…For one, work in other organisms has shown that CRE is capable of excision and recombination over huge distances [50,12] or even between different chromosomes [13]. In T. brucei, this approach could be used, for example, to delete large tandem gene arrays.…”
Section: Extensions Of Cre/loxpmentioning
confidence: 99%
“…As the enzyme requires no additional co-factors, it has been adapted for genetic manipulation in myriad contexts, including yeast and human cells, in vitro and in vivo [7] (reviewed in [8][9][10]). Most notably, the CRE/loxP system has been used for removing selectable markers [11], excising large tracts of genomic DNA [12], triggering chromosomal rearrangements [13] and integrating exogenous DNA to a specific locus [14], none of which has been achieved in Trypanosoma brucei.…”
Section: Introductionmentioning
confidence: 99%
“…The first mice lacking RASSF1 were made by Smith et al (88) who generated a targeting vector to the mouse chromosome syntenic to the minimal region of human chromosome 3p21.3 deleted in lung tumors, this 370-kb deletion knocked out 12 genes including rassf1. Heterozygous mice with this contiguous gene deletion were viable and fertile; however, the homozygous null embryos died before 13.5d.p.c.…”
Section: Microtubules Adhesion and Migrationmentioning
confidence: 99%
“…These results suggest that ''humanised'' Trp53 mutations have a greater impact on lung tumour progression than complete Trp53 loss [18,19]. Targeting genes deleted early in human lung tumorigenesis, such as the complete cluster at chromosome 3p21.3, showed that heterozygous deletion for this 370 kb region showed no obvious predisposition for lung cancer development albeit homozygous deletion caused embryonal lethality [20]. A more specific deletion of candidate tumour suppressor genes on chromosome 3 like RassF1a, FHIT and VHL, showed that 31% of RassF1a -/-mice produced spontaneous mainly lymphomas but also lung adenomas [21].…”
Section: Transgenic Mice First Generationmentioning
confidence: 90%